NEW CONCEPT OF THE EARTH'S OUTER/INNER CORE BOUNDARY - Ovtchinnikov V.M.; Krasnoshchekov D.N.; Kaazik P.B. (My University, 2007)
Seismological studies of the past few years demonstrate that the structure of the Earth’s inner core is much more complex than was accepted in standard models (PREM, IASPEI91, and others). In these models, the outer/inner core boundary (ICB) is sharp with jumps in density and primary/shear wave velocity. In this paper, we present the results of measurement of different parameters of subcritical short-period PKiKP waves reflected from the ICB and give a model explanation of the peculiarities. The main conclusion is in the fact that the ICB is a region with structure, and we suggest its main elements.